1989
DOI: 10.1042/bj2610083
|View full text |Cite
|
Sign up to set email alerts
|

Insulin effects on apolipoprotein B production by normal, diabetic and treated-diabetic rat liver and cultured rat hepatocytes

Abstract: 1. The effect of insulin on apolipoprotein (apo B) secretion was studied in 24 h recirculating liver perfusions of isolated normal, diabetic and insulin-treated diabetic rats. In single perfusions from each group apo B accumulated in the media in a linear fashion. 2 In perfusions of normal rat livers, when the medium contained insulin plus cortisol, apo B production was significantly inhibited (by 35.8%), demonstrating a hormone effect on apo B secretion. 3. In perfusions of diabetic-rat livers, apo B producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 43 publications
4
43
2
Order By: Relevance
“…In order to determine ifthe previously observed reduction in apo B secretion by livers derived from diabetic rats was due to an effect on apo B translation, we examined apo B synthesis in corresponding cultures ofprimary rat hepatocytes. We have previously demonstrated that the reduced hepatic secretion of apo B by liver of diabetic rats is retained by corresponding primary hepatocytes (28,29). Liver perfusions to prepare hepatocytes were carried out 1 h apart so that hepatocytes derived from control and diabetic livers could be cultured under identical experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to determine ifthe previously observed reduction in apo B secretion by livers derived from diabetic rats was due to an effect on apo B translation, we examined apo B synthesis in corresponding cultures ofprimary rat hepatocytes. We have previously demonstrated that the reduced hepatic secretion of apo B by liver of diabetic rats is retained by corresponding primary hepatocytes (28,29). Liver perfusions to prepare hepatocytes were carried out 1 h apart so that hepatocytes derived from control and diabetic livers could be cultured under identical experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…VLDL composition is altered in streptozotocin-induced diabetes with a marked reduction in apo E content (29,31,36) which may be a contributory factor to the catabolic defect, as apo E is an important ligand for hepatic lipoprotein receptors (37). Hepatic secretion of VLDL lipid (36,(38)(39)(40)(41) and apo B and E is substantially reduced in both primary cultures of hepatocytes (28,29) and perfused livers derived from diabetic rats (28,36). These findings suggest that the hyperlipidemia of experimental diabetes is primarily a result of the accumulation of intestinally derived chylomicrons and VLDL, and suggest further that the contribution of apo B-containing lipoproteins to the plasma by the liver in the hypoinsulinemic diabetic state is relatively small.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…One possible mechanism to account for the lower postprandial change in overall total TAG concentration following lunch compared to breakfast is suppression of VLDL-TAG secretion by the liver. This is supported by the observation that addition of insulin to cultured cells (Durrington et al, 1982;Dashti & Wolfbauer, 1987;Sparks et al, 1989;Byrne et al, 1991;Salhanick et al, 1991) and acute hyperinsulinaemia in human subjects (Vogelberg et al, 1978;Lewis et al, 1993Lewis et al, , 1994Shumak et al, 1988;Malmstrom et al, 1997a) suppressed VLDL secretion. Furthermore, Malmstrom et al (1998) showed that hyperinsulinaemia suppressed secretion of VLDL 1 leading to a differential increase in VLDL 2 secretion.…”
Section: Discussionmentioning
confidence: 84%